PAI-AI Trinity of Knowledge: An Examination of Artificial Intelligence in Islamic Religious Education through the Lens of the Philosophy of Science - Waluyo; Khomsin; Tanfirul Khoiri (Kopertais Wilayah X Jawa Tengah, 2025)
A conceptual model that operationally combines contemporary artificial intelligence (AI) literacy with the philosophical framework of Islamic science for the context of religious learning does not yet exist. This research aims to develop a conceptual framework between PAI and AI from the perspective of the Philosophy of Science. The research method is by conducting a structured literature review (scoping review) followed by conceptual synthesis using triangulation analysis. The results of the research resulted in a conceptual framework of the PAI-AI Trinity of Science that integrates three main dimensions. First, epistemic, which is the ability to verify, validate, and contextualize AI-generated knowledge in the sharia corridor, including tracking scientific sanad and source validity. Second, ethics, namely the application of the principles of maqasid al-shariah and Islamic manners in AI human interaction, which includes the protection of human benefits, justice, and honor. Third, axiology, which is the orientation of the use of AI for moral, useful, and sustainable educational purposes according to the vision of Islamic education. In conclusion, the unification of the philosophical tradition of Islamic science with AI literacy and explainable AI (xAI) in education can be translated into curriculum competency design that includes aspects of knowledge, skills, and attitudes; management of digital tools and resources; and a sustainable evaluative research agenda. This framework is expected to be a reference for the development of an Islamic Religious Education curriculum that is adaptive to technological disruptions, but still rooted in Islamic scientific values and principles.